Use of imaging technique and direct tensile test to evaluate moisture damage properties of warm mix asphalt using response surface method. (1st February 2017) - Hamzah, Meor Othman; Teh, Sek Yee; Golchin, Babak; Voskuilen, Jan
Graphical abstract: Highlights: 3-D imaging technique gives precise quantification of the adhesion failure of WMA. At higher mixing temperature, lower adhesion failure and higher DTS were obtained. Lower adhesion failure and DTS were observed at higher test temperatures. Abstract: This paper presents a 3-D imaging technique to quantify the adhesion failure due to moisture on the fractured surfaces of WMA mixtures that were tested for direct tensile strength (DTS). An experimental matrix was developed based on the central composite design for two factors: mixing temperatures of WMA and test temperatures (5 °C, 15 °C and 25 °C) of specimens. Specimens were subjected to 1 Freeze-Thaw (F-T) cycle prior to testing. Adhesion failure and strength behavior of the specimens were analyzed using the Response Surface Method. The effects of mixing and test temperatures on the percent adhesion failure, DTS and fracture energy of WMA were found to be significant. Adhesion failures of WMA prepared with polymer modified binder were lower than mixtures prepared with unmodified binder. At higher mixing temperature, lower percent adhesion failure was observed, while at lower mixing temperature, lower DTS was obtained. Lower adhesion failure and DTS were observed at higher test temperatures.